1 × 8 MEMS Flexible integrated optical device for optical fiber‐based networking applications. Issue 2 (21st December 2012) - Chen, Qinghua; Chen, Yingjun; Wu, Wengang; Li, Yanmei; Li, Li; Yan, Guizhen; Hao, Yilong
Abstract A 1 × 8 MEMS (micro‐electronic mechanical system(‐based flexible integrated optical device with optical switch and variable optical power attenuating functions has been proposed to optimally serve optical fiber‐based networking applications.The device manipulates the light with binary‐slope mirrors driven by compound electrostatic actuator. The optical models for switching and attenuating are investigated, respectively. Performances of the fabricated devices assembled with ball‐lensed fibers are measured and discussed. Measurements reveal that the insertion loss of the device is less than 2.8 dB and the controllable attenuation range is up to 39 dB, respectively. Moreover, polarization‐dependent loss is less than 0.8 dB in the whole attenuation range. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:231–236, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27293